"Do I Really Need to Go to Rehab? I'd say No, No, No.": Estimating Price Elasticities of Convalescent Care Programs - Nicolas R. Ziebarth (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This study is the first to estimate the price elasticities of demand for both medical rehabilitation programs and treatment at health spas. In Germany, the Statutory Health Insurance (SHI) covers both forms of therapy if administered in authorized medical facilities on referral from a physician. While health resort stays are prescribed to recover from general symptoms of poor health and are preventive in character, medical rehabilitation implies recovering from a specific illness or accident. From 1997 onwards, the German government more than doubled the copayments for both types of health care services from DM 12 (e6.14) to DM 25 (e12.78) per day for those insured under the SHI. Using longitudinal microdata from the German Socio-Economic Panel Study (SOEP), this exogenous price variation allows us to study the causal effects on demand, since we have a sound control group available. The data suggest that pull-forward effects in 1996 accounted for up to one-fifth of the subsequent decrease in demand. Taking this anticipation effect into account, we show that the reform induced a decrease in total demand of about 20 percent. We estimate the price elasticity for rehabilitation programs that aim at preventing work incapacity to be about -0.15, whereas the elasticity for rehabilitation programs for recovery from work accidents lies around -0.30. In contrast, the price elasticity for treatment at health spas is elastic and lies between -1 and -2.5.
Keywords: H51; I1; I18; J22; 330; Convalescent care; health spa; medical rehabilitation; price elasticities; SOEP